Experimental and numerical study on the leaching of pesticides into the groundwater through a porous medium: Effects of transport parameters - Khoula Haddad; Abdelhak Gheid; Djamel Haddad; Kafia Oulmi (My University, 2019)
This study aims to investigate, experimentally and numerically, the pesticide transport through the soil in unsaturated zone. The movement of pesticide is described with one dimensional model. The transport equation incorporates terms accounting for diffusion –convection, adsorption and reaction. The first objective of this work was to identifies the effects of the parameters transport such us; the dimensions first order degradation coefficient (µ), the peclet number (ρe) and the dimensionless mass transfer coefficient (w). The evolution of pesticide concentration in function of depth and time was found by using the non-equilibrium transport model. The data obtained show the importance of the adsorbed concentration. The second objective is to find the relation between the concentration and the transport parameters because there is a difficulty of the analytical solution. The solution of the problem was carried out by a numerical approach by using the finite difference method and a Fortran program.